Classification of maximal subalgebras of rank n of the conformal algebra AC(1, n) - Barannyk, A. F.; Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain a complete classification of I-maximal subalgebras of rank n of the conformal algebra AC(1, n).